IMPLEMENTATION OF GUIDED INQUIRY LEARNING TO TRAIN STUDENTS SCIENCE PROCESS SKILLS OF CHEMISTRY EQUILIBRIUM MATERIALS - Ningtiyas, Fienda Ayu (JCER (Journal of Chemistry Education Research), 2019)
This study describes the implementation of guided inquiry learning modelto train students science process skills of chemistry equilibrium materials. The development models using one group pretest-posttest design. Science process skills covering formulate problems, composing hypothesis, identification of variable, planning investigation, data processing, analyze investigation, and draw a conclusion. The results showed that science process skills with impelementation guided inquiry learning model have a average value of formulate problems, composing hypothesis, identification of variable, planning investigation, data processing, analyze investigation, and draw a conclusion is 89.58; 81.25; 87.50; 76.04; 89.58; 67.71; and 86.46. Studentsscience process skills have achieved completeness because gets score ? 80 with 75% scored classical completeness